PENGARUH NAUNGAN DAN PEMBERIAN MULSA TERHADAP PRODUKSI BUAH MELON (CUCUMIS MELO L.) (STUDI KASUS DI PANTAI BUGEL, KABUPATEN KULON PROGO) - Sudaryono Sudaryono (Jurnal Teknologi Lingkungan, 2005)
During the present time, the coastal area is lack of interested by the farmer as the cultivation site of agriculture plant. It is caused by the problem constraint of land physical character and the climate (particularly, micro climate), so that most confined the kinds of plant may be cultivated. The more narrowed of agriculture area, then optimalizing the use of coastal area for developing agriculture is necessary to conduct, although must throungh various means with an environment reengineering, as climate modification, conservation efforts of land moisture, supplying irrigation water, and etc.So that in the research will be implemented the research on the melon plant cultivation with various treatment.But, these condition of micro climate can be manipulated or reengineered with using simple technology in shape of closed shade, so that can be created an ideal condition for cultivation requirements. The result show that melon plant cultivated under the shade with sprinkler irrigation and drip irrigation gives the highest result that is 325 kg/70 m2 or 4,65 kg/m2, the melon planted under the shade + sprinkler irrigation + mulse the result 272 kg/70 m2 or 3,89 kg/m2, while the lowest result is that planted without using the shade with sprinkler irrigation and drip irrigation : 200 kg/m2 or 2,86 kg/m2.